THE LEADERSHIP OF THE MADRASAH HEAD IN IMPROVING TEACHER PERFORMANCE AT MA HIDAYATULLAH BAAR - Amar Ma’ruf (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to find out the leadership style and the strategy used by the head of the school to improve the performance of teachers in the high school with God's guidance. The results of this research indicate that the application of the leadership style of the head of the school is an adaptation to her job as the head of the school. This means that many methods are applied to improve the performance of teachers in the high school God's guidanceThe strategy used is to make conditions and conditions conducive to the work environment, promote harmonious, cooperative relations with society and the business world, improve discipline for all teachers, encourage teachers' enthusiasm to continuously develop creativity in education, give thanks and appreciation to teachers, strictly conduct admission selection for new teachers, and provide guarantees Caring for teachers and evaluating all the activities that have been implemented.